PROTOTIPE SISTEM PENGUKUR KUALITAS TEGANGAN JALA-JALA LISTRIK PLN - Wisnu Djatmiko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
A prototype measuring system voltage quality of the power line based Arduino Uno is proposed to be able to measure and display the VMAX, VEFF, and Frequency using LCD, and realized by 4 sub-system: (1) full-wave rectifier using a diode bridge with a load resistor and pasif low-pass filter to generate VDC; (2) full-wave rectifier using a diode bridge with a load resistor to generate pulses waves of power line; (3) LCD systems board based on IC HD44780 LCD controller; and (4) Board Arduino Uno R3 which serves to calculate and display the value VMAX, VRMS, and the frequency of the power line to LCD. The prototype system has been created and tested can measure voltage of power line in Faculty of Engineering, State University of Jakarta with a value VMAX = 383 Volt, VRMS = 203 Volt, and a frequency of 50Hz is displayed on the LCD and has been compared by using a Digital Multi Meter Sanwa CD800a and PC-Oscilloscope Instrustar ISD205B with an error rate below 1%. Keywords: Line power quality measuring system based Arduino Uno, PLN line voltage parameters, Arduino Uno Application.